2015
DOI: 10.1103/physrevb.91.174305
|View full text |Cite
|
Sign up to set email alerts
|

Majorana braiding dynamics in nanowires

Abstract: Superconductors hosting long-sought excitations called Majorana fermions may be ultimately used as qubits of fault-tolerant topological quantum computers. A crucial challenge toward the topological quantum computer is to implement quantum operation of nearly degenerate quantum states as a dynamical process of Majorana fermions. In this paper, we investigate the braiding dynamics of Majorana fermions on superconducting nanowires. In a finite size system, a nonadiabatic dynamical process dominates the non-Abelia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(62 citation statements)
references
References 62 publications
0
62
0
Order By: Relevance
“…Thus, braiding success and ZBCP are conceptually connected with dissipation playing a central role. While one might argue that braiding experiments differ fundamentally from conductance experiments since the latter depends on Γ L and the former does not, the existing braiding proposals [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] requires the presence of Majorana fermion tunneling in a key way. The Majorana tunneling enters through the tri-junctions in the Majorana braiding proposals.…”
Section: Braiding and Tunneling Conductancementioning
confidence: 99%
See 1 more Smart Citation
“…Thus, braiding success and ZBCP are conceptually connected with dissipation playing a central role. While one might argue that braiding experiments differ fundamentally from conductance experiments since the latter depends on Γ L and the former does not, the existing braiding proposals [51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] requires the presence of Majorana fermion tunneling in a key way. The Majorana tunneling enters through the tri-junctions in the Majorana braiding proposals.…”
Section: Braiding and Tunneling Conductancementioning
confidence: 99%
“…Indeed several proposals have been put forth in the literature for probing the non-Abelian braiding properties of MZMs [24,[51][52][53][54][55][56][57][58][59][60][61][62][63][64][65], and experimental efforts are currently underway to carry out MZM braiding to test their non-Abelian properties. An observation of the non-Abelian braiding properties would go a long way in establishing the existence of true MZMs in nanowires.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, during the braiding the statistic disorder can in general bring about local rotation on the MKPs, with, however, the rotating angles for γ 1 ,γ 1 and γ 2 ,γ 2 being opposite (details are found in the supplementary material [37]). Thus, a generic The non-Abelian braiding of MKPs is confirmed by that the magnitude η(t) = γ1(0)|γ1(t) |t=2T = −1 after a full braiding at t = 2T (similar for other Majorana modes) [7,39,40]. The adiabatic condition is satisfied in that…”
mentioning
confidence: 91%
“…Recently, there have been some advances in this direction. [243][244][245][246][247][248][249][250][251][252][253] The effects of superconducting fluctuations on Majorana fermion states have also been studied recently. [254][255][256][257] It was revealed that the topological degeneracy associated with Majorana fermions is maintained even for the case of quasi-long-range order with power-law decay of the superconducting correlation, for which the total electron charge is conserved, and the phase of the superconducting gap fluctuates.…”
Section: Discussionmentioning
confidence: 99%